Analysis of Propulsion System Modernization Strategy via the KRI X Repowering Program to Enhance Warship Operational Readiness - Nur Rokhmat; Sudirman; Ali Azhar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The operational readiness of warships is closely linked to the reliability and performance of their propulsion systems, whereas aging naval platforms commonly experience degradation that reduces operational effectiveness and increases maintenance requirements. This study aims to formulate a propulsion system modernization strategy through a repowering program for KRI X. A descriptive qualitative design was applied using primary data from in-depth interviews with seven purposively selected informants and observations, supported by secondary data from document analysis. Interview data were coded and analyzed using NVivo 12 Plus, while internal and external factors were evaluated through SWOT analysis. The results show significant degradation in the main engine, gas turbine, gearbox, and controllable pitch propeller (CPP), which adversely affects speed, endurance, maneuverability, propulsion reliability, and operational readiness. The SWOT analysis positions the program in the Weaknesses–Opportunities (WO) quadrant, indicating a Turn-Around Strategy that uses modernization opportunities to overcome internal weaknesses. Repowering is therefore an appropriate strategic and cost-effective approach to improve propulsion reliability and long-term operational readiness, provided that it is supported by logistics, maintenance, personnel competence, and organizational policy.